Deletion of Phd2 in Myeloid Lineage Attenuates Hypertensive Cardiovascular Remodeling. Issue 3 (18th June 2013) - Ikeda, Jiro; Ichiki, Toshihiro; Matsuura, Hirohide; Inoue, Eriko; Kishimoto, Junji; Watanabe, Aya; Sankoda, Chikahiro; Kitamoto, Shiro; Tokunou, Tomotake; Takeda, Kotaro; Fong, Guo‐Hua; Sunagawa, Kenji
Abstract : Background: Hypertension induces cardiovascular hypertrophy and fibrosis. Infiltrated macrophages are critically involved in this process. We recently reported that inhibition of prolyl hydroxylase domain protein 2 (PHD2), which hydroxylates the proline residues of hypoxia‐inducible factor‐α (HIF‐α) and thereby induces HIF‐α degradation, suppressed inflammatory responses in macrophages. We examined whether myeloid‐specific Phd2 deletion affects hypertension‐induced cardiovascular remodeling. Methods and Results: Myeloid‐specific PHD2‐deficient mice (MyPHD2KO) were generated by crossing Phd2 ‐floxed mice with LysM‐Cre transgenic mice, resulting in the accumulation of HIF‐1α and HIF‐2α in macrophage. Eight‐ to ten‐week‐old mice were given N G ‐nitro‐L‐arginine methyl ester (L‐NAME), a nitric oxide synthase inhibitor, and Angiotensin II (Ang II) infusion. L‐NAME/Ang II comparably increased systolic blood pressure in control and MyPHD2KO mice. However, MyPHD2KO mice showed less aortic medial and adventitial thickening, and macrophage infiltration. Cardiac interstitial fibrosis and myocyte hypertrophy were also significantly ameliorated in MyPHD2KO mice. Transforming growth factor ‐β and collagen expression were decreased in the aorta and heart from MyPHD2KO mice. Echocardiographic analysis showed that left ventricular hypertrophy and reduced ejection fraction induced by L‐NAME/Ang II treatment in control mice were not observed in MyPHD2KO mice. Administration of digoxin that inhibits HIF‐α synthesis to L‐NAME/Ang II‐treated MyPHD2KO mice reversed these beneficial features. Conclusions: Phd2 deletion in myeloid lineage attenuates hypertensive cardiovascular hypertrophy and fibrosis, which may be mediated by decreased inflammation‐ and fibrosis‐associated gene expression in macrophages. PHD2 in myeloid lineage plays a critical role in hypertensive cardiovascular remodeling.